2011
DOI: 10.1002/pssc.201100487
|View full text |Cite
|
Sign up to set email alerts
|

Carrier transport mechanism of AlGaN/GaN Schottky barrier diodes with various Al mole fractions

Abstract: The evolution of the dominant carrier transport mechanism of Alx Ga1‐xN/GaN Schottky barrier diodes with increasing Al mole fraction x (x = 0.2, 0.3, 0.4, and 0.5) is investigated. The Schottky barrier height (SBH) linearly increases with the work function of Schottky metal with the slope factor of ∼0.5 irrespective of x. The SBH, the ideality factor, and the reverse leakage current, however, show an increasing deviation from the predicted values given by the thermionic‐emission theory as x increases. The XPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…25 On the other hand, some other studies reported that the electron affinities of GaN and AlN are 4.2 eV and 2.05 eV, respectively. 23,26 Therefore, the calculated SBH value is dependent on the value of Al x Ga 1−x N electron affinity used in the calculation. figure (denoted by a green diamond).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 On the other hand, some other studies reported that the electron affinities of GaN and AlN are 4.2 eV and 2.05 eV, respectively. 23,26 Therefore, the calculated SBH value is dependent on the value of Al x Ga 1−x N electron affinity used in the calculation. figure (denoted by a green diamond).…”
Section: Methodsmentioning
confidence: 99%
“…These results of ideality factor and reverse leakage current lead to the conclusion that the dominant carrier transport mechanism for the Schottky contacts changes sensitively with the change in electrical properties (e.g., reverse leakage current) caused by the structural defects. 26 …”
Section: -5mentioning
confidence: 99%
“…Hence, the Ni-and Au-free gate metal stack is necessary to realize AlGaN/GaN HEMTs in the Si CMOS process line. So far, many Ni-and Au-free gates, including Ti, 5 Cr, 5 Pt, 6 Pd, 6,7 WSi, 7 Ir, 7,8 TaN, 9 and ITO, 9 have been evaluated for the fabrication of AlGaN/GaN HEMTs and Schottky barrier diodes (SBDs). Compared to other materials, the TiN exhibits many advantages such as large metal work function ($5 eV), 10 high thermal stability, 10 and process compatibility to both dry and wet etching processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the Ni/Au‐free gate is required to realize GaN HEMTs in the Si CMOS process line. Researchers have tried Ni/Au‐free gates include Ti, Cr, Ir, Re, Pd, Pt, ITO, TaN, W, WN x , and TiN for the fabrication of AlGaN/GaN HEMTs . Compare with other materials, TiN has a lot of advantages, such as: (i) large work function (∼5 eV ); (ii) compatibility to various CMOS processes, e.g., dry etching, wet etching, sputtering, etc.…”
Section: Introductionmentioning
confidence: 99%